The Influence of Financial Ratios on Dividend Policy in Banking Companies with Firm Size as a Moderating Variable - Adam Putra Oka; Ade Widiyanti (Riset Akuntansi dan Bisnis Indonesia, 2026)
Purpose: This study aims to examine the effect of profitability, leverage, and liquidity on dividend policy, with firm size as a moderating variable in banking companies listed on the Indonesia Stock Exchange (2021–2023). Methodology/approach: A quantitative approach using secondary data from 47 banking firms (141 observations) was analyzed through multiple linear regression with SPSS, including classical assumption tests and hypothesis testing. Results/findings: The results indicate that profitability, leverage, and liquidity have a positive and significant effect on dividend policy, while firm size also shows a significant role and potential moderating influence on the relationship between financial ratios and dividend policy. Conclusions: Financial performance, particularly profitability, leverage, and liquidity, plays an important role in determining dividend policy, with firm size strengthening these relationships in the banking sector. Limitations: The study is limited to the banking sector, a short observation period (2021–2023), and selected financial ratios, which may not fully capture all determinants of dividend policy. Contribution: This research contributes to the literature by providing empirical evidence on dividend policy determinants in Indonesian banking and highlighting the moderating role of firm size for investors and corporate decision-making